SISTEMA DE ATENDIMENTO AOS ADOLESCENTES EM CONFLITO COM A LEI: UM ESTUDO COMPARATIVO ENTRE MOÇAMBIQUE E BRASIL - Francisco, Tomás Xavier José (2014)
This dissertation deals with the system of care for children in conflict with the law, making a comparative study between Mozambique and Brazil, taking as a historic landmark, the constitutional changes brought these two countries in 2004, for the case of Mozambique and in 1988, for the case of Brazil. These constitutional changes meant that subsequently adopt these two countries, an environment conducive to promoting and protecting the rights of the child and adolescent legal framework. This is in general, and more specifically in cases of children in conflict with the law, through a system of care that adequately meets the adolescent offenders. It was in this context that exists in 1990, in Brazil the adoption status of children and adolescents, commonly known as ACE. For the case of Mozambique, a law that can equate to a statute, called the Law for the Promotion and Protection of the Rights of the Child (LPPRC) and the Law of Jurisdictional Organization for Minors, in 2008 approved. The work is structured in three chapters, namely: The first chapter talks about aspects of State, Rule of Law, sovereignty, globalization, fundamental rights and brief approach to Mozambique and Brazil, in terms of geography, political, social and economic. The second chapter presents considerations about the history of the rights of children and adolescents in the world, Mozambique and Brazil; in the third chapter, we addressed properly on the system of care for children in conflict with the law of Mozambique and Brazil. Also work presents conclusions and references. For the preparation of the dissertation, we use as a methodology, descriptive research, preceded by an initial exploratory study and documentary research.